STUDIES ON FRACTIONS OF METHANOL EXTRACTS OF TUBERCLE BACILLI : II. TOXIC AND ALLERGENIC PROPERTIES OF FRACTIONS EMPLOYED AS ANTITUBERCULOUS VACCINE - Williams, Curtis A. (The Rockefeller University Press, 1960)
Fractions of methanol extract which had been previously demonstrated to increase the resistance of mice to experimental tuberculosis have been subjected to an examination of their toxic and allergenic properties. The criteria for toxicity were: (a) production of inflammatory skin reactions in guinea pigs; (b) induction of weight loss in mice by intraperitoneal injection; and (c) depression of resistance to staphylococcus infections in mice. Allergenicity of a preparation was investigated by (a) its ability to evoke a hypersensitive skin response in guinea pigs previously sensitized with whole tubercle bacilli; and (b) its capacity to induce hypersensitivity to one or more of its components when injected under appropriate conditions into guinea pigs. Fraction F I, a preparation precipitated from methanol extract by slow concentration at 45°C., was found to possess some toxicity and some allergenicity by all of the criteria employed. Subfraction F I-P, precipitated from aqueous suspensions of F I by 33 per cent ethanol and 0.5 per cent NaCl, was apparently the F I component responsible for these activities. The saline-ethanol-soluble subfraction, F I-S, was neither toxic nor allergenic by the tests performed. These findings were considered of particular interest inasmuch as F I-S, despite its small yield, had been shown earlier to be the most active single substance used as vaccine to increase resistance to experimental tuberculosis in mice.